Pelatihan Penggunaan Aplikasi Akuntansi Digital Pada UMKM Palangka Raya pada CV. Aneka Buah Segar - Lenlioni, Liling; Rahman, Rahman; Hidayati, Hidayati (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
The purpose of this training is to enhance the company's financial management skills through the use of technology. In the training, participants are taught how to use the Manager IO application to record financial transactions, prepare financial reports accurately, and conduct financial analysis. The results of the training show that participants are able to understand and apply basic accounting concepts more effectively, which in turn supports better decision-making. The implementation of this application is expected to improve operational efficiency and the financial health of CV. Aneka Buah Segar, thereby strengthening the business's competitiveness in the market